2014
DOI: 10.1002/jmv.24056
|View full text |Cite
|
Sign up to set email alerts
|

Rubella outbreak in the union territory of Chandigarh, North India

Abstract: Rubella virus outbreaks usually occur when a large numbers of susceptible individuals accumulate. The disease presents clinically with fever and maculopapular rash. The present study reports the investigation of rubella outbreak in a modern and well-planned village near Chandigarh, North India. The blood samples were collected from 39 cases with febrile rash and from 15 age and sex matched healthy controls residing in the same locality and subjected for the detection of Rubella IgM and IgG antibodies by Enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These vaccination campaigns will be conducted in four phases: the first phase during July-December 2015 covering 10 states, the second phase during January-June 2016 covering 18 states, the third phase during July-December Limited studies are available on rubella virus genotyping from India. Recent study from Chandigarh city showed circulation rubella virus genotype 1a [Singh et al, 2015] and previous studies from Andhra Pradesh, Karnataka, Kerala, Maharashtra, and Tamil Nadu states showed circulation of genotype 2B (NIV Unpublished Data). Testing of stored IgM-positive serum samples has provided a means to obtain baseline genotype information on wildtype rubella viruses .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These vaccination campaigns will be conducted in four phases: the first phase during July-December 2015 covering 10 states, the second phase during January-June 2016 covering 18 states, the third phase during July-December Limited studies are available on rubella virus genotyping from India. Recent study from Chandigarh city showed circulation rubella virus genotype 1a [Singh et al, 2015] and previous studies from Andhra Pradesh, Karnataka, Kerala, Maharashtra, and Tamil Nadu states showed circulation of genotype 2B (NIV Unpublished Data). Testing of stored IgM-positive serum samples has provided a means to obtain baseline genotype information on wildtype rubella viruses .…”
Section: Discussionmentioning
confidence: 93%
“…Limited studies are available on rubella virus genotyping from India. Recent study from Chandigarh city showed circulation rubella virus genotype 1a [Singh et al, ] and previous studies from Andhra Pradesh, Karnataka, Kerala, Maharashtra, and Tamil Nadu states showed circulation of genotype 2B (NIV Unpublished Data). Testing of stored IgM‐positive serum samples has provided a means to obtain baseline genotype information on wild‐type rubella viruses [Rota et al, ].…”
Section: Discussionmentioning
confidence: 99%